Diagnosis and Surveillance of Barrett's Esophagus: Addressing the Transatlantic Divide - Ghaus, Saad; Neumann, Helmut; Muhammad, Humayun; Tontini, Gian Eugenio; Ishaq, Sauid (Digestive Diseases and Sciences, 2016)
Barrett's esophagus is a premalignant condition of the esophagus leading to esophageal adenocarcinoma. No consensus exists between the UK and USA concerning the diagnosis of Barrett's esophagus. Although the diagnostic procedure is common, the required findings and diagnostic criteria vary. Both guidelines require endoscopy showing columnar epithelia lining the esophagus, but the US guidelines require the additional finding of intestinal metaplasia on biopsy to confirm diagnosis. Achievement of a consensus is of particular importance due to the established progression from Barrett's esophagus to esophageal adenocarcinoma. Of further importance is the increasing incidence of esophageal adenocarcinoma, a condition with poor overall survival, leading to various opinions on the utility of surveillance in patients.A review of the vast array of literature revealed that substantial evidence exists in favor of both diagnostic criteria; hence, there is no easy way to identify the "correct" method of diagnosing Barrett's esophagus. USA recommends surveillance of Barrett's esophagus, whereas UK does not advocate it unless dysplasia is present. Surveillance was found to be effective, but this varied as did cost-effectiveness. Further research into diagnostic methods for Barrett's esophagus is needed to address areas of limited understanding, such that agreement can be reached and practice standardized. Surveillance was generally advocated, but with different criteria and time intervals, and new methods are being evaluated.
EVALuna2:2156